Valuasi Ekonomi dan Pengembangan Manajemen Kolaboratif dalam Pengelolaan Gurun Telaga Biru Pulau Bintan - Ayu Dewi Karuniawati (Sekolah Vokasi, Universitas Gadjah Mada, 2022)
The research held in Gurun Telaga Biru, Kabupaten Bintan, Bintan, Kepulauan Riau. The aim is to understand the economic value of Gurun Telaga Biru and also collaborative management which can be applied in order to develop the area as a sustainable tourism. Gurun Telaga Biru is part of industrial park area belongs to PT Suryabangunpertiwi (SBP) with 4.000 hectare land bank. Gurun Telaga Biru has 50 hectares wide which plan as a green belt of industrial park, knowing that its location is closed to Bintan airport. It means that the area is not for industrial factory or other tall building, which will affect the airplane transport circulation.The research applied is mixed method which is mixed analysing from observation, interview and support by quantitative data using Maple 2017 to understand the economic value and tourists’ willingness to pay for Gurun Telaga Biru. PT SBP can use the result of Total Economic Value as data review, in order to decide whether keeping the area as an idle land or developing it as a nature-based tourist destination. The Total Economic Value of Gurun Telaga Biru is Rp. 493.950.214.550,-.per year by understanding the economic value per meter square is Rp. 862.290,- This number is relatively high if compared to the small effort in preparing the place with proper facilities. Communities can explore the nature without adding others infrastructure. Collect the entrance and parking fee. However, it can be more valuable if they conduct in good collaborative management by providing proper infrastructure such as toilet, parking area, food court and souvenir shop by maintaining the collaboration in business, education and social community.